2012
DOI: 10.3791/3387
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Transcranial Magnetic Stimulation to Study the Human Neuromuscular System

Abstract: Transcranial magnetic stimulation (TMS) has been in use for more than 20 years 1 , and has grown exponentially in popularity over the past decade. While the use of TMS has expanded to the study of many systems and processes during this time, the original application and perhaps one of the most common uses of TMS involves studying the physiology, plasticity and function of the human neuromuscular system. Single pulse TMS applied to the motor cortex excites pyramidal neurons transsynaptically 2 ( Figure 1) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The starting point was the vertex (determined as the point of intersection of half of the nasion-inion line and half of the porion-porion line) and subsequently, the position of the coil was systematically varied in the anterior-posterior and medial-lateral directions in 0.5 cm steps. In the present study, the mean hotspot was found lateral to the vertex (lateral (left): 1.15 ± 0.64 cm, anterior-posterior: 0.02 ± 0.44 cm), which is consistent with previous reports (Strutton et al, 2005;Goss et al, 2012).…”
Section: Electromyography (Emg) and Tmssupporting
confidence: 93%
See 2 more Smart Citations
“…The starting point was the vertex (determined as the point of intersection of half of the nasion-inion line and half of the porion-porion line) and subsequently, the position of the coil was systematically varied in the anterior-posterior and medial-lateral directions in 0.5 cm steps. In the present study, the mean hotspot was found lateral to the vertex (lateral (left): 1.15 ± 0.64 cm, anterior-posterior: 0.02 ± 0.44 cm), which is consistent with previous reports (Strutton et al, 2005;Goss et al, 2012).…”
Section: Electromyography (Emg) and Tmssupporting
confidence: 93%
“…Similar to previous work measuring corticomotor excitability in back muscles (Tsao et al, 2008;Goss et al, 2011;Goss et al, 2012), we determined the intensity that evoked an MEP with a clear silent period after stimulation and a clear peak that was discernible from the background EMG activity in 5 out of 10 trials (Tsao et al, 2008).…”
Section: Electromyography (Emg) and Tmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evaluation of maximal voluntary activation, this method does not provide information about cortico-spinal excitability. Transcranial magnetic stimulation could be used to assess changes at this level [65][66][67] .…”
mentioning
confidence: 99%
“…Perform so-called "hot-spot" techniques to locate TMS-sensitive regions of cortex that produce the greatest amplitude MEPs with the lowest threshold upon stimulation 8,13,14 . Transcranial magnetic stimulation for studying motor systems typically involves stimulating a cortical area that controls movement in a specific body part (e.g.…”
Section: Mep Hot-spot Localization and Mep Threshold Pproceduresmentioning
confidence: 99%